PENERAPAN PRESENTASI MEMORITER DALAM PEMBELAJARAN KETERAMPILAN BERBICARA SISWA SMP UNTUK MENGATASI PROBLEMATIKA CAMPUR KODE - Resti Fauziah; Ika Mustika; Aurelia Sakti Yani (IKIP Siliwangi, 2023)
The background of this research refers to the problem of code mixing in speaking skills learning activities at school. The problem of code mixing between Indonesian and Sundanese is an obstacle experienced by students, especially when presenting in class, so several solutions are needed to overcome it. The aim of this research is to determine the effectiveness of memoriter presentations in improving students' speaking abilities. This research used a qualitative descriptive methodology with twenty-two grade 7 students at SMPN 4 Cibinong as research subjects. Data collection was carried out through observations, interviews and classroom actions. Based on the research results, it shows that memoriter presentations are effective in improving speaking skills in class so that the problem of code mixing can be overcome through language instruction when the presentation is made.